Reversible Akinetic Mutism after Aneurysmal Subarachnoid Haemorrhage in the Territory of the Anterior Cerebral Artery without Permanent Ischaemic Damage to Anterior Cingulate Gyri. (23rd June 2016) - Sibille, François-Xavier; Hantson, Philippe; Duprez, Thierry; van Pesch, Vincent; Giglioli, Simone
Abstract : We report on two cases of transient akinetic mutism after massive subarachnoid haemorrhage due to the rupture of an intracranial aneurysm of the anterior cerebral artery (ACA). In the two cases, vasospasm could not be demonstrated by imaging studies throughout the clinical course. Both patients shared common radiological features: a hydrocephalus due to haemorrhagic contamination of the ventricular system and a mass effect of a subpial hematoma on the borders of the corpus callosum. Patients were also investigated using auditory event-related evoked potentials at acute stage. In contrast to previous observations of akinetic mutism, P300 wave could not be recorded. Both patients had good recovery and we hypothesized that this unexpectedly favourable outcome was due to the absence of permanent structural damage to the ACA territory, with only transient dysfunction due to a reversible mass effect on cingulate gyri.